First insights of the electrocatalytical properties of stepped silver electrodes for the hydrogen evolution reaction - Ruderman, Andres (2013)
The electrocatalytic properties of vicinal Ag(11n) surfaces for the hydrogen evolution reaction are investigated. An analysis of the reactivity as a function of the step density is performed. The rate constants for Volmer and Heyrovsky steps are evaluated from potentiostatic transients. A correlation between the anisotropy of hydrogen adsorption energy for different sites with the non-linear dependence on the step density is established.